Medium-sided games in soccer: Physical and heart rate demands throughout successive working periods - Campos Vázquez, M. A.; Casamichana Gómez, D.; Suárez Arrones, L.; González Jurado, J. A.; Toscano-Bendala, F. J.; León Prados, J. A. (Journal of Human Sport & Exercise, 2017)
This research compared the physical and heart rate demands of three medium-sided games with the same number of players per team (six) but different playing areas throughout four successive working periods. The two games played in relatively larger areas (large and medium) were performed with regular goals and goalkeepers, so the most reduced game (short) was performed without goals. Nine professional soccer players participated in this study. Meaningful differences were found (p<0.05) on the physical demands in the three proposals, with higher values for the games performed on larger areas: maximum speed: 22.8±2.4, 19.8±2.3, and 17.6±1.8 Km/h; and distance covered/min: 120.5±13.4, 103.4±11.2, and 93.8±11.6 m/min in large, medium and short game respectively. There were no differences on the heart rate responses among them. When the physical demands were analysed during the four working periods, the differences could only be seen in large game (p<0.05). The first periods in this proposal showed higher values in distance covered/min, maximum speed, and distance/h in the speed zones 7.0-12.9, 13.0-17.9, and 18.0-20.9 Km/h, and lower values in the zones 0-6.9 Km/h, demonstrating, throughout the periods, the tendency to reduce the distance at high speed and to increase the distance at lower speed. These changes in the activity patterns, related to the period of exercising, could depend on the dimensions of the playing field, thus showing a possible effect of fatigue only in those games played in relative higher areas.